CONTINUITY OF CARE Mrs.R DIFFERENCE OF TFU WITH PREGNANCY AGE AT TUTUN PRATAMA CLINIC SEHATI IN 2024: CONTINUITY OF CARE Mrs.R DIFFERENCE OF TFU WITH PREGNANCY AGE AT TUTUN PRATAMA CLINIC SEHATI IN 2024 - Siti Roslina; Rosmani Sinaga; Eva Ratna Dewi; Herna Rinayanti Manurung (Mitra Husada Health Internasional Conference (MIHHICo), 2024)
This study aims to provide continuous midwifery care for pregnant women, maternity, newborns, postpartum and family planning on an ongoing basis or Continuity of Care (COC). The subjects taken in this study were physiological pregnant women TM III at the first tutun sehati clinic on Mrs. R 24 years old G1P0A0. The method used in this study uses 7 Varney steps based on Hellen Varney including assessment, data interpretation of problems and needs, potential problems, action plans, implementation, evaluation and documentation using the SOAP method. Data collection techniques using primary data include interviews, observation, examination. Based on the results of data research, it can be concluded that in carrying out continuous midwifery care Continuity of Care (CoC) there is no gap between theory and practice.